A retrospective analysis of the role of adjuvant radiotherapy in the treatment of cutaneous melanoma. Issue 10 (2nd October 2016) - Baker, Aaron; Camacho, Fabian; Andrews, Genevieve; Mackley, Heath
ABSTRACT: Melanoma is a significant clinical problem, with rising rates of incidence. Surgery is the mainstay of treatment. The role of adjuvant radiotherapy in the control of locoregionally advanced cutaneous melanoma is controversial. A retrospective study of the Surveillance, Epidemiology, and End Results (SEER) database was performed. Patients with locoregionally confined cutaneous melanoma treated surgically between 2004 and 2009 were evaluated, with cancer-specific and all-cause mortality as primary end points. Propensity score matching was used to match 319 radiotherapy patients with 319 non-radiotherapy controls, stratifying by head and neck (HN) and non-head and neck (NHN) primary. Surgery was primarily by wide excision in both the radiotherapy (51.72%) and non-radiotherapy (53.91%) groups. The majority had nodal disease (82.13% vs. 82.44%). White (91.22% vs. 90.59%) males (70.21% vs. 68.96%) predominated. Average ages at diagnosis were 62.27 (SD 15.93) and 63.02 (SD 16.03). Using Cox proportional hazards models, radiation conferred decreased survival in all-cause (HR 1.44, p < 0.0003), and cancer specific mortality (HR 1.57, p < 0.0002) in combined analysis. The NHN group showed significantly decreased 6-year cancer specific survival (HR 2.05, p < 0.0001) for radiated patients. The HN group showed a non-significant hazard with radiotherapy (HR 1.19, p = 0.307). Meaningful differences not captured in the SEER database may exist between cohorts. Based on available SEER data, routine use of adjuvant radiotherapy should be viewed with caution and reserved for high-risk patients. Future trials evaluating patient quality of life may clarify the benefit of adjuvant radiotherapy in high-risk melanoma populations.